REVIEW : Research on insect biodiversity in Indonesia: Dung beetles (Coleoptera: Scarabaeidae) and its role in ecosystem - SHAHABUDDIN SHAHABUDDIN; PURNAMA HIDAYAT; WORO ANGGRAITONINGSIH NOERDJITO; SYAFRIDA MANUWOTO (Biodiversitas Journal of Biological Diversity, 2005)
Research on insect biodiversity in Indonesia which is known as megabiodiversity still not yet a lot of done. Dung beetles represent one of insect group owning very important ecological role and enough suscebtible to condition change of an ecosistem so that is often made as one of bioindicator. Although it was estimated that there is about 1000 to 2000 species of dung beetle in Indo-Australia archipelago but theexact species number of Indonesiaâ€™s dung beetles not yet been known, since the are more than 17,000 islands in the country and different islands posseses a lot of endemic species. The lack of entomologist especially taxonomist and the limited of identification key available also become the problems of study on dung beetles biodiversity as well as another group of insect in Indonesia. Therefore, we need some effort expected to solve these problem in order to accelarate the research of insect biodiversity in Indonesia.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: biodiversity, insects, dung beetles, Scarabaeidae